Phytosociological framework and conservation value of supratemperate riparian birch forest of the NW Iberian Peninsula. - Rodríguez Guitián, Manuel Antonio; Real, Carlos; Romero Franco, Rosa; Álvarez-Hurtado, Alejandro (Lazaroa, 2017)
We studied the downy birch forests that grow in the headwaters of rivers in the mountains in NW Iberian Peninsula and their differences from other previously described birch forests. To do this, an ordination analysis was done on a data base of 342 relevés (144 unpublished). As a result, four riparian forest associations were recognized in the territory, all of them belonging to the suballiance Saxifrago spathularis-Fraxinenion excelsioris (all. Hyperico androsaemi-Alnion glutinosae, ord. Alno-Fraxinetalia excelsioris, cl. Salici-Populetea). Two associations (Carici reuterianae-Betuletum celtibericae and Violo palustris-Betuletum pubescentis) have been previously described, but the other two (Chaerophyllo hirsuti-Betuletum pubescentis and Valeriano officinalis-Betuletum pubescentis) are described here for the first time. We characterized their floristic composition, ecological features and distribution, and evaluated their conservation value under the criteria of the 92/43/CEE Community Directive, and with regard to national and regional lists of protected species.